2021
DOI: 10.1016/j.talanta.2021.122609
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in detection technologies for COVID-19

Abstract: Corona Virus Disease 2019 (COVID-19) is a highly infectious respiratory illness that was caused by the SARS-CoV-2. It spread around the world in just a few months and became a worldwide pandemic. Quick and accurate diagnosis of infected patients is very important for controlling transmission. In addition to the commonly used Real-time reverse-transcription polymerase chain reaction (RT-PCR) detection techniques, other diagnostic techniques are also emerging endlessly. This article reviews the current diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“… Broughton et al (2020) , De Smet et al (2021) , Fozouni et al (2020) , Han et al (2021) , Yoo et al (2021) and Zhang et al (2020a) .…”
Section: Uncited Referencesmentioning
confidence: 99%
“… Broughton et al (2020) , De Smet et al (2021) , Fozouni et al (2020) , Han et al (2021) , Yoo et al (2021) and Zhang et al (2020a) .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Han et al (2021) divide the COVID-19 detection technology broadly into nucleic acid-based, serological-based detection methods, and CT imaging-assisted diagnosis [ 45 ]. However, another study by Etiene et al suggested that detection of COVID-19 can be categorized into viral antigen and antibody [ 46 ].…”
Section: Advances In the Diagnosis Of Covid-19mentioning
confidence: 99%
“…Nucleic acid-based detection methods include real-time RT-PCR, digital polymerase chain reaction (dPCR), metagenomics next-generation sequencing (mNGS), reverse transcription‐loop‐mediated isothermal amplification (RT-LAMP), and clustered regularly interspaced short palindromic repeats (CRISPR). Each of these methods has advantages and disadvantages, but in terms of time, the fastest result is CRISPR followed by RT-LAMP and the longest is mNGS ( Table 1 ) [ 45 47 ]. Syamsun et al (2022) used a rapid molecular testing (RMT) cartridge to detect the COVID-19 nucleic acid in corpses ( Table 1 ) [ 48 ].…”
Section: Advances In the Diagnosis Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of rapid and cost-effective SARS-CoV-2 detection systems is critical to control the unabated pandemic. Although many coronavirus disease 2019 (COVID-19) detection methods have been reported so far [1],…”
Section: Introductionmentioning
confidence: 99%